Enhancing quality in plastic manufacturing: Six sigma application to polybox containers - Priyanti, Nadia Nabila; Saragih, Johnson; Mayusda, Idriwal (OPSI, 2025)
Historical production data from November 2021 to February 2022 revealed that polybox plastic containers suffered from a 2.84% defect rate, exceeding the company’s 2% threshold. This study applies the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology to enhance product quality. The Define phase utilized SIPOC and Critical to Quality (CTQ) diagrams to outline quality characteristics. In the Measure phase, P and U Control Charts established a baseline performance with a Defect Per Million Opportunities (DPMO) of 8,420 and a sigma level of 3.89. The Analyze phase employed Fishbone diagrams and Failure Mode and Effects Analysis (FMEA) to isolate root causes. High Risk Priority Numbers (RPN) highlighted worker carelessness (294), welding inaccuracies (252), and manual handling issues (210). Consequently, the Improve phase implemented new Standard Operating Procedures (SOPs), welding guidelines, and hand-truck trolleys. Post-implementation monitoring during the Control phase showed immediate improvements: the DPMO dropped to 6,305, and the sigma level increased to 3.99. These findings confirm the efficacy of Six Sigma interventions in reducing manufacturing defects and aligning production with quality standards.